Predictors of health‐related quality of life over time among pediatric hematopoietic stem cell transplant recipients. Issue 10 (22nd June 2016) - Loiselle, Kristin A.; Rausch, Joseph R.; Bidwell, Sarah; Drake, Sarah; Davies, Stella M.; Pai, Ahna L. H.
Abstract: Background: Advances in hematopoietic stem cell transplantation (HSCT) have contributed to increased survival for pediatric patients. However, there are inconsistent findings regarding the impact of HSCT on health‐related quality of life (HRQOL) outcomes for children. This study aimed to establish trajectories of HRQOL following HSCT and identify predictors of the HRQOL course. Procedure: Ninety caregivers of a child who received HSCT (mean age = 6.42 years) for various oncologic, immunologic, and metabolic conditions completed questionnaires regarding family psychosocial functioning and child HRQOL at the time of discharge from HSCT and follow‐up HRQOL at four additional time points. Results: There was a significant change in overall HRQOL in 3 months postdischarge, with the greatest improvement in physical functioning. Caregiver stress and social support, and child psychosocial problems predicted changes in HRQOL over time. Conclusions: These results point to potentially modifiable factors that are related to the course of HRQOL following HSCT, and interventions aimed at these factors should be implemented.